Optimal Allocation of Capacitors in Radial Distribution Systems with Distributed Generation - Franco, John F. [UNESP]; Rider, Marcos J. [UNESP]; Lavorato, Marina [UNESP]; Romero, Ruben [UNESP]; Gualteros, M. V.; Rodriguez, PYA; Aldana, A. (Ieee, 2011)
This paper presents a mixed-integer linear programming approach to solving the optimal fixed/switched capacitors allocation (OCA) problem in radial distribution systems with distributed generation. The use of a mixed-integer linear formulation guarantees convergence to optimality using existing optimization software. The results of one test system and one real distribution system are presented in order to show the accuracy as well as the efficiency of the proposed solution technique.
Keywords: Distribution system optimization; optimal allocation of capacitors; mixed-integer linear programming; CPLEX; AMPL